Hotels Segmentation Strategies for BtoB Marketing: a Study in São Luís-MA - Ferreira, Luciana Brandão; Ikeda, Ana Akemi (Revista Turismo em Análise, 2012)
The focus of this article are the travels by business reasons, which have great importance forthe development of tourism and hostelry even in localities with natural and cultural touristattractions, as is the case of the city of São Luís-MA. The objective was to study thesegmentation strategies used by hotels to Business to Business Marketing. For this, is done amultiple case study in two large hotels in the city belonging to internationals chains –Pestana São Luís Resort Hotel and Quality Grand São Luís Hotel – through an exploratoryqualitative research. The primary data collection was done through personal interviews withsales managers of the respectives hotels. The analysis of cases is based on three main points:the marketing hotels structure, the forms of segmentation used and the marketing actionsdirected to the business public. The segmentation strategies are used by the hotels, but theyare based in the use of fewer variables: current sales volume, potential of future sales and thesales channel. The specific actions for the business public are incipient, even considering thegreat importance of this market.